2019
DOI: 10.3847/2041-8213/ab288a
|View full text |Cite
|
Sign up to set email alerts
|

On the Interpretation of Parker Solar Probe Turbulent Signals

Abstract: In this letter we propose a practical methodology to interpret future Parker Solar Probe (PSP) turbulent time signals even when Taylor's hypothesis is not valid. By extending Kraichnan's sweeping model used in hydrodynamics we derive the Eulerian spacetime correlation function in magnetohydrodynamics (MHD) turbulence. It is shown that in MHD, the temporal decorrelation of small-scale fluctuations arises from a combination of hydrodynamic sweeping induced by large-scale fluid velocity δ u 0 and by the Alfvénic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Figure 2 also contains the time series of the parameter = δv rms / √ 2v sc calculated from 1-hour intervals, where v sc is the magnitude of the solar wind velocity in the spacecraft frame. This is the same parameter as in the model of Bourouaine & Perez (2019), in which perpendicular sampling is assumed so v sc ∼ v sc⊥ , and in which the Taylor hypothesis is valid for 1. The model also assumes Gaussian random sweeping and anisotropic turbulence k ⊥ k , and it is valid when tan(θ BV ) δv rms /v A , where θ BV is the angle between B 0 and the mean solar wind velocity in the spacecraft frame.…”
Section: Turbulence Propertiesmentioning
confidence: 99%
“…Figure 2 also contains the time series of the parameter = δv rms / √ 2v sc calculated from 1-hour intervals, where v sc is the magnitude of the solar wind velocity in the spacecraft frame. This is the same parameter as in the model of Bourouaine & Perez (2019), in which perpendicular sampling is assumed so v sc ∼ v sc⊥ , and in which the Taylor hypothesis is valid for 1. The model also assumes Gaussian random sweeping and anisotropic turbulence k ⊥ k , and it is valid when tan(θ BV ) δv rms /v A , where θ BV is the angle between B 0 and the mean solar wind velocity in the spacecraft frame.…”
Section: Turbulence Propertiesmentioning
confidence: 99%
“…To estimate the corresponding perpendicular correlation lengths from the obtained correlation times we invoke Taylor's Hypothesis. Although the ratio V A /V ⊥ ∼1 (where V ⊥ is the perpendicular velocity of the spacecraft seen in the plasma frame), Bourouaine & Perez (2019, showed that Taylor approximation can still be valid if the dimensionless parameter…”
Section: Turbulence Characteristics In Sb and Nsb Intervalsmentioning
confidence: 99%
“…Due to the comparable Alfvén and solar wind, and spacecraft speeds, it is unclear whether the Taylor hypothesis is valid for PSP observations during its perihelion (Narita et al 2013;Bourouaine & Perez 2018Chhiber et al 2019). Recent work from Chaspis (2020, to be submitted) suggests the Taylor hypothesis may not be applicable when PSP is below 40 solar radii (0.19 AU).…”
Section: Introductionmentioning
confidence: 99%